Efeito da adição fracionada de Dimetil formamida e das curvas de congelamento na viabilidade in vitro pós-descongelamento do espermatozoide eqüino. - Jair Perez Osorio (2006)
The aim of this research was to evaluate the efficiency of three times of fractionate addition of 5%, the dimethyl formamide to the half seminal extender modified base INRA 82, and its interaction with the time of balance and the rates of freezing in the criopreservation of equine spermatozoa. Ejaculates of six stallions was used to test three times of addition of the dimethyl formamide; Time 1: addition of the tenth part ofdimethyl formamide to each the one minute in the time of ten minutes; Time 2: addition of the tenth part of dimethyl formamide to each the two minutes in the time of twenty minutes; Time 3: addition of the tenth part of dimethyl formamide to each the three minutes in the time of thirty minutes. Completing the average period of one hour and eight minutes in ambient temperature since the beginning until addition of the crioprotectan all the samples had been cooled until 5°C using one scheme computerized to a rates of cooling 0,25°C/min. 3 different procedures for the freezing had been tested: a) without time of additional balance 5°C and freezing 4cm above of the nitrogen level fifteen minutes, and posterior submersion of the samples in nitrogen liquid; b) with timeof additional balance 5°C of forty five minutes and freezing 4cm above of the nitrogen level fifteen minutes, and posterior submersion of the samples in nitrogen liquid e; c) with time of additional balance 5°C of forty five minutes and freezing computerized to one rates of -10°C/min ties -127°C per fifteen minutes, and posterior submersion of the samples in nitrogen liquid. The thawing was made 52°C per ten seconds, followed ofimmersion in bath-Maria 37°C per thirty seconds. Immediately post thaw the parameters of total motility, motility progressive and spermatic vigor were evaluated under microscopy 400X. The integrity of the plasmatic membrane of the tail was evaluated through the hiposmotic swelling test and the functional and structural sperm membrane integrity were evaluate by the fluorescent dyes, carboxyfluorescein diacetateand propidium iodide respectively. The spermatozoa were also evaluated in the temperature resistance. Was not observed significant difference (P> 0, 05) enters the three times of addition and enters the freezing rates. The results allow concluding that the changes of the time of addition of the crioprotectan of fractionate form and the curve of freezing did not modify the equine spermatic viability evaluated in vitro..